Viability of probiotic micro-organism Lactobacillus acidophilus in dairy chocolate dessert and its action against foodborne pathogens - Luciana Justo Beserra Rosa (Ciência Rural, 2015)
ABSTRACT:The ability to produce antimicrobial factors is considered an important feature of probiotic microorganisms. Bacteriocins, hydrogen peroxide, acetic acid and lactic acid are examples of these substances. The present research aimed to develop probiotic dairy desserts (DD) with Lactobacillus acidophilusand evaluate the viability of this strain, as well as its action on food pathogens. Treatments with and without interactions between L. acidophilusand pathogenic Gram-negative bacteria (Salmonellasp. andEscherichiacoli O157:H7) and Gram positive (Bacillus cereusand Staphylococcus aureus) were produced. The products were stored at a temperature of 8°C and analyzed at the times 24, 48, 72 hours, 7 days and 28 days (at 28 days, only T1 was analyzed because the other products were deteriorated). In an analysis of the potential for development of new products, the dairy dessert with L. acidophiluswas considered a probiotic product. Assessment of the counts of pathogens in dairy desserts with or without L. acidophilusshowed different behaviors of these products in response to pathogens, which could be justified by a possible action of bacteriocins or microbial competition, but there has been no overall reduction or reduction up to a safe level. It is concluded that the probiotic products developed reduced significant food pathogens, but not up to safe levels. Thus, we emphasize the importance of the use of quality tools in the development and monitoring of dairy desserts.